Application of Contextual Teaching and Learning Model to Improve Disposition and Creative Thinking Skills of High School Students - Puji, Evilya Suraning; Sukarso, AA; Merta, I Wayan (Jurnal Pijar Mipa, 2024)
Facing the challenges of the 21st century, learning must be able to produce learners into creative individuals to solve problems. The ability to think creatively is closely related to a person's character or creative habits; good character can trigger good skills. This study aims to determine how applying the Contextual Teaching and Learning (CTL) model improves students' creative disposition and creative thinking skills. The method in the form of Quasi-Experimental Design uses Pre-test and post-test control Group Design on as many as 64 X students at one of Aikmel State High Schools, NTB. The 32-person experimental class used the CTL model of the guided inquiry method, and the 32-person control class of the discussion method. Data on students' creative dispositions were collected using creative disposition questionnaires given before and after good treatment in both groups. Data on students' creative thinking skills were collected with a creative thinking skills test developed referring to the Torrance Creative test. The data were obtained and analyzed using the t-test to determine the comparison of the two classes and the N-gain test to see the improvement in each class. The results showed significant differences in creative disposition and creative thinking skills between the experimental class and the control class. Increased creative disposition in the experimental class with an N-gain of 0.45 means an increase in the medium category and an N-gain of 0.08 in the control class, which means an increase in the low category. Meanwhile, the creative thinking skills of experimental class students amounted to an N-gain of 0.48, which means there was an increase in the medium category, and an N-gain of 0.05 in the control class, which means there was an increase in low theory. This study concludes that applying the CTL model can improve creative disposition and thinking skills.